2016
DOI: 10.1590/1518-8345.0882.2733
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the profile of emergency contraception users

Abstract: AbastractObjective: to discern the profile of the Spanish Emergency Contraceptive users (EC). Design: systematic review of contraceptive use in the Spanish population. Data Source: Spanish and international databases, between January 2006 - March 2011. Keywords: Contraceptives, Postcoital pills, emergency contraception, levonorgestrel, data collection. Study selection: original papers, letters to the editor in which stated aims were the description, prediction or measurement of variables related to EC use. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
(10 reference statements)
3
2
0
2
Order By: Relevance
“…We observed that, in most cases, women used this medication within 24 h of having unprotected sex (87.2%), which is comparable to that obtained in other studies [14,17]. We also observed that repeat use of this medication was accompanied by more risky sexual behavior in users who take EC more than 48 h after unprotected sex compared with those who obtain it during the first few hours, including a lower percentage of users who use condoms, and a higher percentage who use no contraceptive method.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We observed that, in most cases, women used this medication within 24 h of having unprotected sex (87.2%), which is comparable to that obtained in other studies [14,17]. We also observed that repeat use of this medication was accompanied by more risky sexual behavior in users who take EC more than 48 h after unprotected sex compared with those who obtain it during the first few hours, including a lower percentage of users who use condoms, and a higher percentage who use no contraceptive method.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to the age profile of the users, although we did not detect age differences between first-time and repeat users in this study, a higher overall mean age was observed in women who took EC (26.9 ± 7.8 years) in relation to data from most national and international studies, where it was 20-24 years [11,14,20,21]. However, 7.7% of EC dispensations were provided to minors, similar to that found in other studies [17]. These latter data are accompanied by a high percentage of cases that did not use any regular contraceptive method.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These incidents were related to the participants’ first sexual experiences and to the inability to correctly use a condom. Condom breakage seems to be a repeated theme in other studies, including a review performed by these authors [ 22 ] as well as in other international studies [ 6 , 12 , 23 ].…”
Section: Discussionmentioning
confidence: 78%
“…Nossos resultados mostraram que grande parte das mulheres, que usaram a AE anteriormente, usou até três vezes na vida. Em revisão feita por Amengual et al (2016), sobre o perfil de uso da AE de mulheres espanholas, a maioria declarou ter usado a AE somente uma vez, o mesmo encontrado por outros estudos (Daniels, Jones, Abma, 2013). Portanto, todos os estudos apontam que o uso da AE parece ser esporádico e não um método utilizado rotineiramente.…”
Section: Uso Anterior Da Ae E Fatores Associadosunclassified